Perceived influences on smoking behaviour and perceptions of dentist‐delivered smoking cessation advice: A qualitative interview study. Issue 5 (6th July 2020) - Holliday, Richard; McColl, Elaine; Bauld, Linda; Preshaw, Philip M.; Sniehotta, Falko F.; McDonald, Suzanne
Abstract: Objectives: Many factors lead to the commencement and maintenance of smoking, and better understanding of these is relevant in the management of oral health, particularly as smoking cessation advice (SCA) from the dental team is a key component of patient care. Whereas most previous research has focused on dental professionals' perceptions of providing SCA, and identified facilitators and barriers to its provision, there has been more limited research focusing on patients' perceptions of receiving SCA in the dental context. Accordingly, this study aimed to explore the views of smokers with periodontitis receiving dentist‐delivered SCA. Methods: One‐to‐one, semi‐structured interviews were conducted with a purposive sample of 28 adults who smoked tobacco and had recently received SCA during dentist‐delivered periodontal therapy. Participants were sampled to reflect a range of ages and smoking behaviours. The interview schedule was based on the Theoretical Domains Framework (TDF) to explore perceived influences on smoking behaviour. Interviews also elicited participants' views on dentist‐delivered SCA. Interviews were audio‐recorded, transcribed verbatim and analysed thematically, drawing on the TDF. Results: A broad range of perceived influences on smoking behaviour emerged from the data. Influences were allocated into seven prominent TDF domains: (i) social influences (family and friends, social pressures); (ii) social/professional role and identity (secret smoking); (iii) knowledge (experiences/perceptions of smoking cessation medications); (iv) environmental context and resources (social, home and workplace environment, cost of smoking, resentment towards authority); (v) emotions (stress management, pleasure of smoking and fear of quitting); (vi) nature of the behaviour (habitual nature, link to other behaviours, smell); and (vii) beliefs about consequences (health). With regard to views on dentist‐delivered SCA, five main themes emerged: (i) opportunistic nature; (ii) personal impact and tangible prompts; (iii) positive context of cessation attempt; (iv) lack of previous support; and (v) differences between dentist‐delivered SCA and other setting SCA. Conclusions: Smokers with periodontitis consider that a wide range of factors influence their smoking behaviour. Dentist‐delivered SCA was supported and positively received. Important aspects included the opportunistic nature, personal impact, use of tangible prompts and positive context (of the quit attempt). Future research should focus on optimizing dentist‐led smoking cessation intervention based on the themes identified.